The study of interchangeability of liquefied natural gas (LNG) with other fuels - Deirdre, James Damu (2010)
Natural gas interchangeability is the key subject in the industry today and most recently Liquefied Natural Gas (LNG) has emerged as a major source and differs substantially from domestically produced gas. Interchangeability means the characteristics of a design that allow direct placement of one item without requiring any modification. This research was a challenge, as it is difficult to find the suitable equipment and available equipment in the lab is limited to a lab scale only as the objective is to investigate to what degree LNG in its gaseous form is interchangeable and to show Wobbe Index (WI) is a measure of the fuel interchangeability. From the research that has been conducted, the key parameters used to investigate the interchangeability of a fuel gas WI, Calorific Value (CV), Air Fuel Ratio (A/F) and CARI (Combustion Air Requirement). This research is conducted by experiment, studying the methane as LNG and LPG (at different composition) using Boys calorimeter to find the CV and WI. Then, the Flame Propagation and Stability Unit are used to measure each fuel gases A/F and CARI index. As expected, the result showed that LNG has higher WI value that is 304.787 Btu/Ft3 when compared to LPG with the value of 238.08 Btu/Ft3, followed with Propane with the value 228.51 Btu/Ft3 and Butane with the value of WI 210.816 Btu/Ft3. As a conclusion, LNG has much better characteristics in interchangeability factor and higher heating value meaning higher Wobbe Index which is better performance in terms of interchangeability when compared to other fuel. It is safe to say LNG provides higher energy to the burner and provides much efficient as well as safer combustion process. The accuracy and the efficiency of this research could be improved by using a metered or digitalizing the Boy’s Calorimeter and well as customizing the flame properties for the flame propagation and stability unit at a constant flame color and rate.